Ultrastructural study of ectomycorrhizas on Pinus caribaea Morelet. var. hondurensis Barr. & Golf. seedlings - Gross, Eduardo; Casagrande, Lilian I. Thomazini [UNESP]; Caetano, Flávio Henrique [UNESP] (Sociedade Botânica do Brasil, 2004)
A ultraestrutura das ectomicorrizas formadas por Pinus caribaea var. hondurensis inoculado com Pisolithus tinctorius (Pers.) Coker & Couch e Telephora terrestris (Ehrenb.) Fr. foi analisada antes do transplantio dessas mudas para o campo, com o intuito de verificar se o fungo estava estabelecido nas raízes. Os fungos ectomicorrízicos inoculados formaram um manto compacto e bem desenvolvido nas raízes laterais. Nas hifas desse manto foram observados vacúolos, núcleos e septos dolipóricos, enquanto que no citoplasma das hifas da rede de Hartig, que ficam adjacentes às células corticais, foram freqüentemente observados vários núcleos, retículo endoplasmático e mitocôndrias polimórficas. Células corticais altamente vacuolizadas, contendo gotículas de material elétron-denso, apresentaram núcleo e algumas organelas na sua estreita região citoplasmática periférica. As ectomicorrizas de P. caribaea var. hondurensis apresentaram características ultraestruturais de uma associação compatível e fisiologicamente ativa.

The ultrastructure of ectomycorrhizas formed between Pinus caribaea var. hondurensis inoculated with Pisolithus tinctorius (Pers.) Coker & Couch and Telephora terrestris (Ehrenb.) Fr. was analyzed just before the transplant of these seedlings to the field to ascertain if fungi are established in the roots. Ectomycorrhizal fungi formed a well-developed compact mantle in lateral roots. Vacuoles, nuclei and dolipore septa were observed in mantle hyphae and numerous nuclei, endoplasmatic reticulum and polymorphic mitochondria were frequently located in the cytoplasm of Hartig net hyphae adjacent to plant cortical cells. Highly vacuolated cortical cells contained droplets of electron-dense material, nucleus and some organelles were observed in a narrow region of peripheral cytoplasm. The ectomycorrhizas of P. caribaea var. hondurensis exhibited typical ultrastructural characteristics of a compatible and physiological active association.
Estudo ultraestrutural de ectomicorrizas em plântulas de Pinus caribaea Morelet. var. hondurensis Barr. & Golf.
Keywords: ectomicorriza; Pinus caribaea var. hondurensis; ultraestrutura; Pisolithus tinctorius; Thelephora terrestris; ectomycorrhiza; Pinus caribaea var. hondurensis; ultrastructure; Pisolithus tinctorius; Thelephora terrestris